(untitled) (European Bison Conservation Newsletter, 2015)
The aim of this study was histological characteristic of corpus luteum in lowland European bison (Bison bonasus bonasus) and its comparison with histological structure of corpus luteum in European moose (Alces alces). The study group consisted of 7 females of European bison 5–20 years old living in Białowieża Forest. Histology of European bison corpora lutea were compared with group of 7 females of European moose 4–12 years old living in north-eastern Poland. All animals included in this study were in early pregnancy. The weight and size of each ovary was measured. The surface of each gonad was examined for presence of corpora lutea. Then, the ovaries were fixed in 10% neutral buffered formalin, processed by common paraffin technique and stained with haematoxylin and eosin. Microscopic analysis has shown significant interspecies differences in corpus luteum histology. The corpus luteum in E. bison has more organized structure and more abundant connective tissue compared to that of moose . Large lutein cells and small lutein cells of E. bison corpus luteum have lower metabolic activity than in moose. However, detailed analysis of histological structure of E. bison corpus nucleus at all stages of pregnancy are necessary to draw more definitive conclusions and further studies are needed.